Lucía Puenzo, una narradora anfibia para la literatura y el cine - María José Punte (Cuadernos LIRICO)
Lucía Puenzo, born in Buenos Aires (Argentina) in 1976, is both a filmmaker and a writer. She has published six novels, plus a book of short stories. She is the maker (either as director, screenwriter, or both at the same time) of five feature films, shorts, several series for television. She adapted two of her novels, The Fish Child and Wakolda. Beyond the question about how the written word and the audiovisual are positioned in each of these formats, her work enables the question about how a space of intermediation functions, its narrative and an aesthetic made by imbrication, based on the polysemy of what we usually understand as image.